Penyuluhan Perawatan dan Perbaikan Sepeda Motor Injeksi di Desa Pundensari Kecamatan Purwodadi - Widiyatmoko Widiyatmoko; Mike Elly Anitasari (Universitas Muhammadiyah Purworejo, 2019)
The purpose of activity is to provide community knowledge about the maintenance and repair of injection motorcycle, and developing the skills and creativity. these activities are related to automotive. The object is automotive community service; teenager, youth in Pundensari with 19 participants. The problem is to solve three stages; preparation, implementation, and evaluation. In preparation phase, the problem is carried out by analyzing the problem and need. The second stage, implementation, it is divided into several sessions; opening, coaching of brief theory, and interactive discussion. The method is the coaching material about how to maintain and repair injection motorcycles by discussions, interactive discussion about problems in injection motorcycle. The third is evaluation by listening the audience. The results can be described in the following indicators: 1) The implementation is conducive, good, and smooth, 2) Based on the result of feedback from the participants, it is found that this activity is needed by the participants as well. It is important and economic because of the long distance from Pundensari the official center of service and maintenance both Honda and Yamaha, 3) Participants got new knowledge about how to care and repair Injection motorcycle.